Anti-thymocyte globulin treatment augments 1,25-dihydroxyvitamin D3 serum levels in patients undergoing hematopoietic stem cell transplantation - Saraiva de Matos, Carina; Peter, Katrin; Weich, Laura; Peuker, Alice; Schoenhammer, Gabriele; Roider, Tobias; Ghimire, Sakhila; Babl, Nathalie; Decking, Sonja; Güllstorf, Martina; Kröger, Nicolaus; Hammon, Kathrin; et al. (Frontiers in immunology, 2022)
Application of anti-thymocyte globulin (ATG) is a widely used strategy for the prevention of graft-versus-host disease (GvHD). As vitamin D3 serum levels are also discussed to affect hematopoietic stem cell transplantation (HSCT) outcome and GvHD development, we analysed a possible interplay between ATG treatment and serum levels of 25-hydroxyvitamin D3 and 1,25-dihydroxyvitamin D3 in 4 HSCT cohorts with different vitamin D3 supplementation. ATG is significantly associated with higher serum level of 1,25-dihydroxyvitamin D3 around HSCT (day -2 to 7, peri-transplant), however only in patients with adequate levels of its precursor 25-hydroxyvitamin D3. ATG exposure had no impact on overall survival in patients supplemented with high dose vitamin D3, but was associated with higher risk of one-year treatment-related mortality (log rank test p=0.041) in patients with no/low vitamin D3 supplementation. However, the difference failed to reach significance applying a Cox-model regression without and with adjustment for baseline risk factors (unadjusted P=0,058, adjusted p=0,139). To shed some light on underlying mechanisms, we investigated the impact of ATG on 1,25-Dihydroxyvitamin D3 production by human dendritic cells (DCs) in vitro. ATG increased gene expression of CYP27B1, the enzyme responsible for the conversion of 25-hydroxyvitamin D3 into 1,25-dihydroxyvitamin D3, which was accompanied by higher 1,25-dihydroxyvitamin D3 levels in ATG-treated DC culture supernatants. Our data demonstrate a cooperative effect of 25-hydroxyvitamin D3 and ATG in the regulation of 1,25-dihydroxyvitamin D3 production. This finding may be of importance in the context of HSCT, where early high levels of 1,25-dihydroxyvitamin D3 levels have been shown to be predictive for lower transplant related mortality and suggest that vitamin D3 supplementation may especially be important in patients receiving ATG for GvHD prophylaxis.
Gesehen am 25.08.2022